APLIKASI SISTEM PERHITUNGAN PEMAKAIAN LISTRIK DENGAN MENGGUNAKAN PHP - Mahendra, Galih; ., Sujito (DINAMIKA DOTCOM, 2014)
This study was conducted to facilitate the customer gets the information about the calculation of electricity bill quickly and easily. The purpose of this study was the realization Electricity Calculation System Application Using PHP. The research used of data collection method and basic calculation methods PLN. Applications to be built is a web-based using php and mysql. The results show that the system electricity consumption calculations can be applied perfectly. This application can be used to determine the cost of postpaid electricity consumption calculation based on the number of Â KWH, and prepaid electricity consumption based on the amount of money deposited. The results of this research is the establishment of electricity consumption calculation system applications web based.Â Keywords: php, mysql, calculation process, simulation